Strategi Peningkatan Minat Nasabah Dalam Penggunaan Internet Mobile Banking (Studi Kasus pada Bank Syariah Mandiri di Lhokseumawe) - Hamdiah Hamdiah; Likdanawati Likdanawati (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study is to describe the strategies that increase customer interest in using internet mobile banking at Bank Syariah Mandiri Lhokseumawe branch offices. The strategies carried out by Bank Syariah Mandiri to increase customer interest in using internet mobile banking is by carrying out promotional activities to introduce services and also retaining customers. Promotion can be conducted by creating advertisements and personal sales. Front liner employees, especially customer service, offer mobile banking services when a customer opens a new account. The obstacles faced in increasing customer interest in using internet mobile banking consist of the ability of customers to use technology and Lack of public knowledge about internet mobile banking facilities so that many customers still do not understand the use of technology.